A delay in vascularization induces abnormal astrocyte proliferation and migration in the mouse retina. Issue 3 (3rd February 2017) - Morita, Akane; Ushikubo, Hiroko; Mori, Asami; Arima, Shiho; Sakamoto, Kenji; Nagamitsu, Tohru; Ishii, Kunio; Nakahara, Tsutomu
Abstract : Background : Astrocytes migrate into the retina through the optic nerve head by means of the axons of retinal ganglion cells, and spread radially toward the peripheral retina. Endothelial cells migrate along the astrocyte cellular network to form the retinal surface vasculature. Here, we examined the effects of a delay in retinal vascularization on the migration and proliferation status of astrocytes in mice.Results : A dose‐dependent delay in retinal vascularization was observed in mice that had been treated with KRN633 (1–10 mg/kg), a VEGF receptor inhibitor, on the day of birth and on the following day. Delayed vascularization resulted in a delay in the astrocyte network formation, and an increase in astrocyte number in the optic nerve head and the vascular front. The increase in the number of astrocytes may be attributed to increased proliferation and delayed migration. These abnormalities in astrocyte behavior correlated with the degree of delay in retinal vascularization. The vascularization delay also led to retinal hypoxia, which subsequently stimulated VEGF leading to an increase in vascular density.Conclusions : These findings suggest that a delay in normal vascularization leads to abnormal astrocyte behavior, which results in the formation of abnormal astrocyte and endothelial cell networks in the mouse retina. Developmental Dynamics 246:186–200, 2017 . © 2016 Wiley Periodicals, Inc. Key Findings: A short‐term postnatal VEGF inhibition disrupts retinal vascularization. Delayed retinal vascularization leads to abnormal astrocyte proliferation/migration. Abnormal astrocyte behavior results in abnormal endothelial cell network formation.